Sexual Dysfunction after Colorectal Surgery - Zigouras, Sophia; Taylor, James P. (Clinics in Colon and Rectal Surgery, 2025)
Sexual health is a key component of well-being and quality of life. Following colorectal surgery, many patients experience sexual dysfunction in the form of difficulty with libido, arousal, pain, and fertility. Autonomic nerve damage can explain many of these symptoms and may be a result of surgical trauma, tumor invasion, chemotherapy and radiotherapy, or pelvic inflammation and infection. An understanding of pelvic neuroanatomy can help prevent direct nerve damage during surgical dissection, but the effects of postsurgical inflammation and ischemia may be unavoidable. Despite the availability of tools for assessing patient-reported sexual health, data to support an informed consent discussion including risks to sexual health, and a multidisciplinary team of sexual health providers who can be involved in management, sexual dysfunction in colorectal surgery patients remains underdiagnosed and inadequately addressed in clinical practice. This represents a key area for quality improvement in delivering holistic and empathic care to the colorectal patient population.
Keywords: sexual dysfunction; autonomic nerves; colorectal surgery; quality of life